Avaliação de genótipos de sorgo sacarino em resposta à aplicação de vinhaça no oeste do Paraná - Corrêia, Arlindo Fabrício (2016)
The sweet sorghum (Sorghum bicolor (L.) Moench) has potential agro-energy and the possibility of multipurpose use in the agricultural sector, however, it has not been widely adopted by farmers nor for ethanol production plants. This study aimed to evaluate the productivity, nutritional composition and silage sorghum as a result of fertilization with vinasse. The research was conducted at the experimental station of PUCPR Câmpus Toledo-PR during the months of november 2014 to august 2015 using the BRS-511, CR-1339 and CR-1342 genotypes. The experimental design the field was a randomized block in a factorial design with 3 additional treatments (3x5+3) with 4 repetitions, totaling 72 plots. The biofertilizer factor consisted of vinasse in natura at doses of 0, 50, 100, 150 and 200 m³ ha-1 and additional treatments of conventional chemical fertilizer application compounds. Productivity variables were: stem length (CCo), stem diameter (DCO), fresh pasta stem (MFCo), fresh pasta broth (MFCa), broth volume (VCa), degrees brix of juice (ºBrix), dry mass of inflorescence (MSI), dry matter of the stem (MSCo), dry mass of leaves (MSF) and total dry matter (MST). To assess the nutritional status analyzed the concentration of macro and micro nutrients N, P, K, Ca, Mg, Mn, Fe and Zn. The silage was held to 170 DAS (days after sowing), with experimental design in blocks with triple factorial (genotype x fertilization x inoculation) with three repetitions totaling 54 plots. At 95 days after the closing of the silage were collected samples for pH analysis, drying and quantification of dry matter content (MS%), crude protein (PB% MS), ether extract (EE% MS), ash (%MS), neutral detergent fiber (FDN% MS), fiber in acid detergent (FDA% MS), lignin (LIG% MS), total digestible nutrients (NDT), dry matter digestibility (DMS), digestible energy (ED) and energy metabolizable (EM). The results indicate the genotypes as the main source of variation, with different results in broth productivity for BRS-511, CR-1339 and CR-1342. Similar results were observed for total soluble solids potential averaging 19.205 °Brix, 14.670 °Brix and 8.579 °Brix. The biomass yield the best results were obtained for CR-1342 (42,960.4 kg ha-1) followed by CR-1339 (31,788.8 kg ha-1) and BRS-511 (18,884.0 kg ha-1) for MST. Leaf analysis showed no significant difference in the application of vinasse compared to chemical fertilizer, only to an increase in Mg content when using the biofertilizer, prevailing differences in results between genotypes. The bromatological results indicate good quality of CR-1339 and CR-1342 hybrids, however, a higher digestibility for the BRS-511 grow crops, not observable difference between the factor fertilization and inoculation